Progress Analysis of Personalized Antiplatelet Therapy in Patients with Coronary Heart Disease Undergoing Interventional Therapy - Ji-tong Yang; Qiu-juan Zhang; Hua Li; Ming-wei Liu (Reviews in Cardiovascular Medicine)
Coronary atherosclerosis (or coronary heart disease [CHD]) is a common cardiovascular disease that seriously damages human health. Percutaneous coronary stent implantation represents the primary treatment option for severe CHD in clinical practice; meanwhile, dual antiplatelet therapy (DAPT) is widely used to reduce the risk of postoperative thrombosis. Although the mechanisms of action of the two most commonly used antiplatelet drugs, aspirin and clopidogrel, remain unclear, clinical studies have shown that some patients are susceptible to stent thrombosis—antiplatelet resistance (high on-treatment platelet reactivity [HTPR])—despite using these drugs. Therefore, screening for HTPR and formulating personalized antiplatelet therapies is necessary. Ticagrelor, indobufen, and rivaroxaban are the most common and safe antiplatelet drugs used in clinical practice, with broad application prospects. This review summarizes the mechanisms of action of existing antiplatelet drugs, reasons for personalized treatment, screening of antiplatelet reactions, and development of novel antiplatelet drugs.